2005
DOI: 10.1177/001440290507100404
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Nonresponders: An Experimental Field Trial of Identification and Intervention Methods

Abstract: First graders (N = 323) participated in an evidence-based classwide reading program (Peer-Assisted Learning Strategies; PALS). Adual-discrepancy approach was used to identify 56 children whose reading performance and growth rates were substantially below those of average readers, indicating they were not responding sufficiently to PALS. This approach reliably distinguished among unresponsive at-risk, responsive at-risk, and average-performing readers. Nonresponders were assigned randomly to one of three increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
201
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(221 citation statements)
references
References 31 publications
13
201
0
7
Order By: Relevance
“…Given this individual variance in responsiveness to intervention (cf. Torgesen, 2000), the dual-discrepancy approach for identifying responders and non-responders to intervention could be relevant (poor performance-level and intervention growth rate compared to age-peers; Fuchs & Fuchs, 1998;McMaster et al, 2005). Based on the previous recommendations, the importance of continuous progress monitoring of skills development , and the study results of sub-study II, a triple-discrepancy approach could also be suggested for identifying non-responders (suggested in sub-study II).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given this individual variance in responsiveness to intervention (cf. Torgesen, 2000), the dual-discrepancy approach for identifying responders and non-responders to intervention could be relevant (poor performance-level and intervention growth rate compared to age-peers; Fuchs & Fuchs, 1998;McMaster et al, 2005). Based on the previous recommendations, the importance of continuous progress monitoring of skills development , and the study results of sub-study II, a triple-discrepancy approach could also be suggested for identifying non-responders (suggested in sub-study II).…”
Section: Discussionmentioning
confidence: 99%
“…A dual-discrepancy approach has been suggested for discriminating between responders and non-responders to intervention (poor performance level and intervention growth rate as compared to age-peers; Fuchs & Fuchs, 1998;McMaster, Fuchs, Fuchs, & Compton, 2005). Nonetheless, children with (or at-risk for) MD are not homogeneous in terms of the deficits associated with MD and responsiveness to intervention (e.g., Jordan et al, 2003;).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations